Педагогическая поддержка деятельности классного руководителя - Шалгимбекова, А.Б. (My University, 2016)
The article deals with the problem of the support of the work of classroom teacher. This is one of the most urgent problems, because the classroom teacher is one of the strongest links in the system of education of the younger generation. The classroom teacher organizes and projects a work of the pupilsin a variety forms of life. The classroom teacher can promptly and effectively respond to the problems of the child, if psychological assistance and educational support are correct.
Keywords: pedagogical support; self-organization; self-realization; social and pedagogical support